Second wave of COVID-19 pandemic in Pakistan; Reasons and mitigation measures - Ejaz Ahmed Khan (Journal of Ayub Medical College Abbottabad, 2021)
The second wave of COVID-19 pandemic is finally here and is spreading rapidly across all regions of Pakistan with an increase in active cases and hospitalization of critical patients. The strict policies enforced across Pakistan in April-June 2020, were followed by gradual ease of the lockdown with many social, political, religious, and regular business activities opening up. This new wave requires urgent national action where the public needs to follow health guidelines. However, both the government and the public are still not taking the pandemic seriously. With a raging pandemic, public is apparently showing very little consideration for preventive measures. There is an increase in social gatherings, out of home activities, holding and attending public gatherings without wearing masks, insisting on shaking hands, lack of physical distancing, and unwilling to pay heed to appeals for caution. The number of COVID-19 cases started climbing with the start of winter. The ground was all set for explosion in number of cases in Pakistan and is likely that circulation of the SARS-CoV-2 will not stop here and it is highly probable that COVID-19 will become a persistent infection if the lessons are not learnt.